Quantifying the differences between gravity reduction techniques. Issue 5 (1st October 2018) - Heath, Philip
Abstract : Gravity data processing (reduction) generally utilises the best-available formulae. New and improved formulae have been introduced over time and the resulting newly processed gravity will not match the old. Additionally, mistakes made in the gravity reduction process, as well as the incompatibilities between various equations, will inevitably lead to errors in the final product. This can mean that overlapping gravity surveys are often incompatible, leading to incorrect geological interpretations. In this paper I demonstrate the magnitude of change that results when different information is introduced at various stages of the gravity reduction process. I have focussed on differences relating to calibration factors, time zones and time changes, height, geodetic datums, gravity datums and the equations involved therein. The differences range from below the level of detection (0.01 mGal) to over 16.0 mGal. The results not only highlight the need to be diligent and thorough in processing gravity data, but also how it is necessary to document the steps taken when processing data. Without proper documentation, gravity surveys cannot be reprocessed should an error be identified. Abstract : This paper demonstrates the magnitude of change that results when different information (relating to calibration factors, time zones and time changes, height, geodetic datums and gravity datums) is introduced at various stages of the gravity reduction process. The differences range from below 0.01 mGal to over 16.0 mGal.